Public discourse and the attitudes of university students towards homosexuality as a sexual orientation - Jordaan, Christina (Department of Communication Science, University of the Free State, 2011)
The legalisation of same-sex marriages in South Africa (1999) was a natural progression from the articles of the South African Constitution (1996), particularly those contained in the Bill of Rights, that safeguard individuals from any form of discrimination based on sexual orientation. A legal right to protection against discrimination does not, however, translate to a society free of prejudice and (covert) discrimination, and this can be clearly seen in the way that deeply biased attitudes towards homosexuality1 emerge in public discourse at the level of the ordinary citizen, as well as the politically powerful. The public statements expressing extreme homophobia by a number of high profile individuals in recent years is of particular concern because it not only communicates prejudicial attitude through message transmission, but reinforces such attitudes amongst the intended audience. This kind of prejudicial communication is particularly insidious because it is impossible to prove cause and effect, even though legislation against hate speech is based on the assumption that speech communication can have a measurable harmful effect. This article explores the attitudes towards alternative sexual orientation of a sample group of 58 third-year B.Ed. students at the Nelson Mandela Metropolitan University. From the research results reported in this article it appears that there is at least an emerging tolerance towards gays and lesbians amongst the sample of educated young South Africans. This is encouraging in view of the promotion of human rights, social justice and inclusion in a democratic South Africa.
Keywords: South Africa; Legislation; Sexual orientation; University students; Discrimination; Attitudes